Pinkwashing Policies or Insider Activism? Allyship in the LGBTIQ+ Governance–Activism Nexus - Karine Duplan (Urban Planning, 2023)
While there has been an increase in the rights and visibility of LGBTIQ+ people in (most) European countries, critiques of what is denounced as instrumentalization by public policies of LGBTIQ+ issues have also developed. In this context, one can ask how to qualify the strengthened relationships between governance and activism. In this article, I propose to explore the paradoxical articulation of the multiple sites from where the cause support can be enacted. Drawing on a Geneva-based ethnographic research project, I use the concept of governance–activism nexus to reflect on the liminal position of public officials in charge of implementing equality agendas. Troubling further the insider–outsider binary divide, I argue that they act towards a discrete queering of municipal governance from the inside, through the practice of allyship in solidarity. In so doing, this article offers future research perspectives for the study of urban/regional LGBTIQ+ activism and politics, while allowing us to question our own position as critical or activist researchers in the field of feminist and queer geographies.